Pengaruh Kompetensi Sumber Daya Manusia, Penerapan Sistem Akuntansi Keuangan Daerah dan Peran Auditor Internal terhadap Kualitas Laporan Keuangan Daerah (Studi Empiris pada OPD Kabupaten Rokan Hilir) - Dewi Astri Sasmita; Nasrizal Nasrizal; M Rasuli (Jurnal Kajian Akuntansi dan Auditing, 2020)
This research was conducted to examine whether the factors of human resource competency, the application of regional financial accounting systems and the role of internal auditors affect the quality of regional financial reports. The study was conducted on officials and employees OPD at the District Rokan Hilir. To examine this reserch’s hypothesis, the author uses the multiple regression analysis by using SPSS version 21.0. The results of this study reveal that there is a positive effect on the variables of competence in human resources, the application of regional financial accounting systems and the role of internal auditors on the quality of regional financial reports.